Cattle adapted to tropical and subtropical environments: Genetic and reproductive considerations - Cooke, Reinaldo F.; Cardoso, Rodolfo C.; Cerri, Ronaldo L. A.; Lamb, G. Cliff; Pohler, Ky G.; Riley, David G.; Vasconcelos, José L. M. [UNESP] (Oxford University Press (OUP), 2020)
Efforts to understand biological functions and develop management schemes specific to Bos indicus-influenced cattle raised in tropical and subtropical environments are critical to meet the increasing global demand for protein. In the United States, B. indicus breeds are mostly used to generate B. indicus × B. taurus crosses with increased thermal and parasite tolerance, while retaining some productive characteristics of B. taurus cattle. Although crossbreeding represents a proven strategy to improve cattle adaptation almost immediately, research has also attempted to identify B. taurus genetics that can withstand subtropical and tropical climates. Reduced milk production and delayed reproductive maturation appear to be related with tropical adaptation of B. taurus breeds, as a means to conserve energy under stressful conditions and limited nutrition. Moreover, longevity may be the ultimate adaptation response to unfavorable environments, and retention of bulls and heifers from proven cows is the recommended strategy to improve longevity in B. indicus-influenced herds. Besides selection for longevity, other aspects should be considered when planning reproductive management in tropical and subtropical regions. Bos indicus and B. taurus breeds have multiple differences pertaining to reproductive function, including age at puberty, ovarian dynamics, and pregnancy development. Nutritional strategies such as the stair-step regimen, and use of exogenous progesterone (P4) inserts are options to hasten puberty attainment of late-maturing B. indicus-influenced heifers. Yet, limited pharmacological alternatives are available for reproductive management of B. indicus-influenced females in the United States, which rely on GnRH-based protocols not specifically designed to the reproductive function of B. indicus breeds. In contrast, hormonal protocols based on exogenous P4, estradiol esters, and equine chorionic gonadotropin are available for use in B. indicus females in South America. These include protocols tailored to prepubertal heifers, anestrous cows, and cycling nulliparous or parous females, which often yield pregnancy rates of 50% to fixed-time artificial insemination. The global dairy industry also faces similar challenges in increasing demand and production as the beef industry. Selection of cows capable of sustaining optimal milk yield, reproductive success, and health status in hot and humid conditions is essential for optimal dairy production in subtropical and tropical regions.
Keywords: Bos indicus; genetics; physiology; reproduction; tropical and subtropical environments